2018
DOI: 10.3389/fevo.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

How Safe Is It to Rely on Macrolophus pygmaeus (Hemiptera: Miridae) as a Biocontrol Agent in Tomato Crops?

Abstract: Omnivorous mirids (Hemiptera: Miridae) are unusual as biocontrol agents, as they feed on both plants and pests. Therefore, extensive knowledge of their ecological behavior is required to maximize their predatory side and to minimize crop damage. Macrolophus pygmaeus is a known predator of small arthropods, used in European tomato crops for more than 20 years. This mirid is currently considered harmless to tomato, although some controversy remains in relation to the status of the species. The aim of this work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…In contrast, Macrolophus species used in biocontrol programs are widely considered harmless [ 1 ]. However, M. caliginosus Wagner can damage tomatoes and cause economic loss through flower and fruit drop [ 48 ] and high densities of M. pygmaeus can cause significant tomato fruit damage, particularly when the plant was infected with Pepino mosaic virus [ 49 , 50 ]. As found with other Macrolophus biocontrol agents, careful management of M. praeclarus numbers may be necessary and further studies should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Macrolophus species used in biocontrol programs are widely considered harmless [ 1 ]. However, M. caliginosus Wagner can damage tomatoes and cause economic loss through flower and fruit drop [ 48 ] and high densities of M. pygmaeus can cause significant tomato fruit damage, particularly when the plant was infected with Pepino mosaic virus [ 49 , 50 ]. As found with other Macrolophus biocontrol agents, careful management of M. praeclarus numbers may be necessary and further studies should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Migration from stems to roots has already been demonstrated for 32A in grapevine [31]. In the case of increased predator density [5], mirid feeding on plants could lead to slight yield losses [16,17]. Mirids were provided with either mock-inoculated or bacterium-inoculated tomato plants as only food source and differences in tomato shoot length after M. pygmaeus-mediated transmission were greater in PsJN-inoculated plants compared to mock-and 32A-inoculated plants.…”
Section: Discussionmentioning
confidence: 85%
“…Macrolophus pygmaeus and N. tenuis have piercing and sucking mouthparts that contain two channels: one to pump salivary fluid into plant tissues and the other to suck sap fluids from the host [13]. These two species frequently complement their carnivore diet with plant sap feeding [14,15], which could also lead to slight yield losses [16,17]. For example, M. pygmaeus feeds mainly on the mesophyll of leaves, stems and fruits, and high population densities caused fruit damage when plants are infected with pepino mosaic virus (PepMV) [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, Moerkens et al (2016) reported that M. pygmaeus, can cause economic damage in tomato crops regardless the presence or absence of prey. In addition, Sanchez et al (2018), reported that high populations of this mirid may lead to a yield reduction due to increased plant feeding. Yet, further research is necessary regarding other species of host plants.…”
Section: Introductionmentioning
confidence: 99%